Analisis Anggaran Pendidikan Provinsi Jambi - Azwan Azwan; M. Surya Hidayat; Syamsuddin H.M (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
Education was essentially non-discriminatory. Education is for all the children of the nation. If there are people who can not get an education, especially basic education of nine years, it is the duty of the government to take action so that no more children of school age are not in school. With the enactment of the nine-year compulsory education program means all Indonesian children nine years of compulsory schooling and compulsory funded by the government. The government has set the education budget is allocated 20% of the APBN or APBD. The case study is the achievement of 20% was never achieved in the education budget in Jambi Province despite budget each year tends to increase. The purpose of this study was to analyze the proportion of the education budget Jambi formula comparison, how big the proportion and deconcentration progress with the development of the formula, is there a relationship between the increase in the education budget with APM and APK with pearson product moment correlation formula and how big the budget needs field education for 8 years to come up with a method of exponential trend. The research yielded information that the average proportion of education budgets to the provincial budget over a period of 12 years by 7,6 percent, and the proportion of development deconcentration lowest occurred in 2010 of 21,3 percent and the largest occurred in 2012 amounted to 228,5 percent, the significance of the correlation results turned out to be the APBN/APBD with APM SD, APK SMP and APK SMA were not significant, while the correlation/relationship between the APBN/APBD with APM SD, APK SMP and APK SMA are very strong while the estimated growth of the education budget in Jambi Provincial APBD for 7 years on average amounted to 23,2 percent.